Krill oil-incorporated liposomes as an effective nanovehicle to ameliorate the inflammatory responses of DSS-induced colitis - Kim, Jin Hee; Hong, Soon Seok; Lee, Myoungsoo; Lee, Eun Hye; Rhee, Inmoo; Chang, Sun Young; Lim, Soo Jeong (International Journal of Nanomedicine, 2019)
Background: Phosphatidylcholine (PC) and Omega-3 fatty acid (Omega-3) are promising therapeutic molecules for treating inflammatory bowel disease (IBD). Purpose: Based on the IBD therapeutic potential of nanoparticles, we herein sought to develop Omega-3-incorporated PC nanoparticles (liposomes) as an orally administrable vehicle for treating IBD. Methods: Liposomes prepared with or without Omega-3 incorporation were compared in terms of colloidal stability and anitiinflammatory effects. Results: The incorporation of free Omega-3 (alpha-linolenic acid, eicosapentaenoic acid or docosahexaenoic acid) into liposomes induced time-dependent membrane fusion, resulting in particle size increase from nm to μm during storage. In contrast, krill oil incorporation into liposomes (KO liposomes) did not induce the fusion and the particle size maintained <250 nm during storage. KO liposomes also maintained colloidal stability in simulated gastrointestinal conditions and exhibited a high capacity to entrap the IBD drug, budesonide (BDS). KO liposomes greatly suppressed the lipopolysaccharide-induced production of pro-inflammatory cytokines in cultured macrophages and completely restored inflammation- impaired membrane barrier function in an intestinal barrier model. In mice subjected to dextran sulfate sodium-induced colitis, oral administration of BDS-entrapped KO liposomes suppressed tumor necrosis factor-α production (by 84.1%), interleukin-6 production (by 35.3%), and the systemic level of endotoxin (by 96.8%), and slightly reduced the macroscopic signs of the disease. Conclusion: Taken together, KO liposomes may have great potential as a nanovehicle for oral delivery of IBD drugs.
Keywords: Animals; Anti-Inflammatory Agents, Non-Steroidal; Budesonide; Caco-2 Cells; Colitis; Cytokines; Dextran Sulfate; Euphausiacea; Fatty Acids, Omega-3; Female; Humans; Lipopolysaccharides; Liposomes; Macrophages; Mice, Inbred C57BL; Oils; Inflammatory bowel disease; Krill oil; Liposomes; Omega-3 fatty acid; Phosphatidylcholine